Jobs for young people : a way to a better future (Commonwealth Secretariat LondonGB, 1987)
Summarizes issues and conclusions relating to youth unemployment, its social and economic effects, and prospects. Examines causes of youth unemployment focusing on the quantitative and qualitative aspects of the demand for and the supply of young people's labour and the differences between the two. Assesses some of the policies and measures governments and others have taken to reduce youth unemployment and makes suggestions for action at the national, international, and Commonwealth levels.
Includes bibliographical references